Distribution and dynamics of the Cynodon dactylon invasion to the cultivated fields of pearl millet in north-central Namibia. (October 2022) - Teshirogi, Koki; Kanno, Miho; Shinjo, Hitoshi; Uchida, Satoshi; Tanaka, Ueru
Abstract: In north-central Namibia, pearl millet cultivation is critical for the subsistence of the local people. In recent years, pearl millet cultivation affected by Cynodon dactylon has been observed in the area. In this study, we examined the background and impact of C. dactylon on agriculture in this region. Our study showed that there would be almost no pearl millet harvest if C. dactylon dominated the fields. The distribution of C. dactylon was spatially skewed within the region, and the degree of weed damage varied between households. Analysis of the distribution of C. dactylon and the land characteristics of each household revealed that the indigenous land unit and the year in which the local people migrated were influential factors. The expansion of C. dactylon is an agronomic problem and is affected by several factors, including the human community structure, diversity of the natural environment, and recent social changes. Highlights: Cynodon dactylon adversely affects pearl millet growth in north-central Namibia. C. dactylon flourishes in soil environments suitable for pearl millet cultivation. Indigenous land units impacts C. dactylon distribution and agricultural production. Expansion of C. dactylon is closely associated with local population migration.